MOBILE GENETIC ELEMENTS IN MICROBIAL GENETICS: MECHANISMS OF HORIZONTAL GENE TRANSFER AND THEIR ROLE IN THE EVOLUTION OF ANTIMICROBIAL RESISTANCE: A MINI REVIEW - Lubna Abdulazeem (Journal of Medical Genetics and Clinical Biology, 2026)
Objective: This mini-review discusses the major types of mobile genetic elements (MGEs), their molecular mechanisms of mobility, their role in horizontal gene transfer, and their contribution to the evolution and dissemination of antimicrobial resistance in microbial populations. Method: The review applies a structured narrative synthesis of the peer-reviewed articles, standard microbiology references, and international surveillance reports cited in the manuscript. Evidence was organized thematically around microbial genome organization, horizontal gene transfer, major MGE classes, genomic islands, antimicrobial resistance dissemination, and genomic approaches for MGE detection and surveillance. Results: The literature indicates that plasmids, transposons, insertion sequences, integrons, integrative and conjugative elements, bacteriophages, and genomic islands form interconnected genetic vehicles that accelerate the acquisition and spread of resistance, virulence, and adaptive traits. Whole-genome sequencing, metagenomics, comparative genomics, and bioinformatics increasingly enable high-resolution tracking of these elements, while CRISPR-Cas systems influence the interaction between microbes and mobile DNA. Novelty: This review integrates the molecular mechanisms, genomic architecture, antimicrobial-resistance consequences, and surveillance implications of MGEs within a single concise framework and highlights their relevance to clinical microbiology, environmental microbiology, and biotechnology.